2016
DOI: 10.1155/2016/2106342
|View full text |Cite
|
Sign up to set email alerts
|

Early Administration of Glutamine Protects Cardiomyocytes from Post-Cardiac Arrest Acidosis

Abstract: Postcardiac arrest acidosis can decrease survival. Effective medications without adverse side effects are still not well characterized. We aimed to analyze whether early administration of glutamine could improve survival and protect cardiomyocytes from postcardiac arrest acidosis using animal and cell models. Forty Wistar rats with postcardiac arrest acidosis (blood pH < 7.2) were included. They were divided into study (500 mg/kg L-alanyl-L-glutamine, n = 20) and control (normal saline, n = 20) groups. Each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…Studies have shown that in many lung and heart diseases, the interference of Gln can repair cardiopulmonary function [ 16 , 17 , 33 ]. In the lung, it had been reported that Gln improve the vascular function and ameliorate inflammation and damage of lung tissues [ 19 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that in many lung and heart diseases, the interference of Gln can repair cardiopulmonary function [ 16 , 17 , 33 ]. In the lung, it had been reported that Gln improve the vascular function and ameliorate inflammation and damage of lung tissues [ 19 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In heart disease research, early administration of glutamine protects cardiomyocytes from Post-Cardiac Arrest Acidosis [ 51 ]. In a CLP rat model, treatment with Gln reduced sepsis-induced cardiac myocyte injury [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A circulação extracorpórea também é uma forma de lesão cardíaca por isquemia e reperfusão, provavelmente por este motivo estes dois últimos autores encontraram desfechos clínicos mais significativos. 26,27 Debates recentes mostram que minimizar o tempo de jejum pré-operatório é uma estratégia segura e eficaz para diminuir inflamação, resposta ao estresse e resistência insulínica. Há diversos trabalhos encorajando o uso de CHO 12,5% nas 2 horas que antecedem a cirurgia, e enriquecer esta bebida com whey protein e/ou glutamina é um tópico com crescente interesse de estudo e promissor para otimizar ainda mais a recuperação operatória.…”
Section: Discussionunclassified
“…[48; 49] Currently, in contrast to previous studies, H. Buter et al [50] have shown an association between plasma Gln levels and severity of clinical condition calculated on the APACHE-IV scale. According to Y. Lin et al, [51 Gln reduces apoptosis of cardiomyocytes and increases their functional activity at low pH. Under experimental conditions, Gln increased the lifespan of rats after asystole.…”
Section: Rgn As a Risk Factor For An Unfavorable Course Of The Patholmentioning
confidence: 99%